2011
DOI: 10.1097/brs.0b013e3181c95047
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Thoracolumbar Injury Classification System in Thoracic and Lumbar Spinal Trauma

Abstract: The TLICS score treatment recommendation matched surgical treatment in 47 of 49 patients (96%). The TLICS was found to correlate to the AO classification. This suggests that the TLICS can be used to classify thoracolumbar trauma and can accurately predict surgical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 11 publications
1
69
0
4
Order By: Relevance
“…In addition, it neither provides prognostic information nor accounts for the neurological status of the patient and, therefore, does not adequately guide surgical decision making. 22 The original concept of instability has been oversimplified to state that it exists if two of three columns are disrupted, thus requiring operative stabilization in these cases. Several studies have, however, shown that non-operative treatment of two-column injuries may achieve a satisfactory outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it neither provides prognostic information nor accounts for the neurological status of the patient and, therefore, does not adequately guide surgical decision making. 22 The original concept of instability has been oversimplified to state that it exists if two of three columns are disrupted, thus requiring operative stabilization in these cases. Several studies have, however, shown that non-operative treatment of two-column injuries may achieve a satisfactory outcome.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] In addition, the AO system does not account for the patient's neurological status, a critical determinant of surgical decision making. 22 TLICS, the most recent classification system for thoracolumbar spine injuries, also has its limitations. Most of the investigations with regard to it have been performed by individuals who were involved with its development, and majority of the published data is based on retrospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…23,71 Both TLICS and SLIC incorporate the same 3 categories of injury characteristics: injury morphology, integrity of the PLC or discoligamentous complex (DLC), and neurological status (Table 1). 44,63 The TLICS and SLIC sum the patient score in each category, and the final score determines the next treatment step. A score < 4 suggests nonoperative management, 4 is borderline, and > 4 is an indication for operative management.…”
Section: Surgical Candidacy and Approachmentioning
confidence: 99%
“…Our analysis also corroborates the results for the reliability of the TLICS/TLISS classification, as excellent results were obtained in regard to agreement between the treatments indicated by the classification and the treatment indicated by the evaluating surgeons, as previously demonstrated in various publications. 10,7,8,12,14,15 We attribute the findings of our study to the fact that the new classification was well established before the case analysis. In addition to receiving the original article and a summary version in Portuguese a week earlier, on the day of the evaluation, the surgeons attended an oral presentation about the TLICS system and received an explanatory summary about it.…”
Section: Discussionmentioning
confidence: 70%